Epidural analgesia for cytoreductive surgery with peritonectomy and heated intraperitoneal chemotherapy. (April 2015) - Piccioni, Federico; Casiraghi, Claudia; Fumagalli, Luca; Kusamura, Shigeki; Baratti, Dario; Deraco, Marcello; Arienti, Flavio; Langer, Martin
Abstract: Purpose: To evaluate epidural analgesia role after cytoreductive surgery with peritonectomy combined with heated intraperitoneal chemotherapy. Methods: 101 patients were retrospectively studied (between 2008 and 2012) to evaluate epidural analgesia effectiveness, tolerability and safety in this surgical context through the assessment of pain, detection of adverse events (nausea, vomiting, itching), temporary motor block, respiratory failure and coagulation profile in the post-operative period. Results: The median duration of epidural analgesia was 5 [range 1–10] days. As regards pain relief, the median verbal numerical scale scores at rest and on movement were below 2 and 5 until the fifth post-operative day, respectively. 13% of patients suffered nausea, 4% vomit, and 1% itching. No bradycardia or respiratory failure event was reported. 9.9% of patients had hypotension episodes. Coagulation reached normality only 3–4 days after surgery. 5 risky accidental dislodgments of epidural catheter occurred (prothrombine time INR > 1.5) without neurological complications. Conclusions: Epidural analgesia ensures adequate pain relief and is well tolerated by patients after cytoreductive surgery with peritonectomy combined with heated intraperitoneal chemotherapy. Hypotension is common in this context and careful monitoring of coagulation parameters, especially in the first 3 days after surgery, is advisable to reduce the risk of neuraxial complications. Highlights: Epidural analgesia ensures adequate pain relief and is well tolerated after CRS and HIPEC surgery. In this context, postoperative hypotensive episodes are frequent in patients with epidural analgesia. Intraoperative developed coagulopathy resolves in 3–4 days after CRS and HIPEC. Careful epidural catheter management is essential to avoid neuraxial complications.